Trismegistia maliauensis H. Akiyama & M. Suleiman (Sematophyllaceae, Musci), a new species from Maliau Basin, Northern part of Borneo - Hiroyuki Akiyama; Monica Suleiman (2003)
A new species, Trismegistia maliauensis H. Akiyama & M. Suleiman is described on the basis of specimens collected at the foot of Maliau Basin, northern part of Borneo (Malaysia, Sabah). It differs from the congener so far reported from Borneo in the green to blackish brown color of plants, sparsely branching and roundly foliated ascending shoots, widely lanceolate, sometimes ovate, stem- and branch-leaves with obtuse apex, and the unique habitat preference to rheophytic zones at riverbeds in lower montane forests.